2021
DOI: 10.3390/f12040401
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Dynamics Assessment of Coarse Wood Debris Subjected to Successional Decay Levels of Three Forests Types in Northeast, China

Abstract: Coarse wood debris (CWD) plays a critical role in forest productivity, nutrient cycling, decomposition, and carbon sequestration, and shapes the carbon pool in the forest ecosystem. However, the elemental composition of CWD varies among different forest types and decay classes for the same dominant tree species (Pinus koraiensis, PK). We compared CWD elemental composition across different forest types (Picea koraiensis-Abies nephrolepis-Pinus koraiensis forest (PAPF), Betula costata-Pinus koraiensis forest (BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
0
0
Order By: Relevance
“…In this study, we found a positive correlation between CWD and soil properties (Figures 1 and 2). Nutrient concentrations generally increased with advancing decay class, a pattern frequently observed in other studies (Khan et al, 2021). This may be due to mass loss, nutrient concentration, rainfall, and root colonization (Osman, 2013).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In this study, we found a positive correlation between CWD and soil properties (Figures 1 and 2). Nutrient concentrations generally increased with advancing decay class, a pattern frequently observed in other studies (Khan et al, 2021). This may be due to mass loss, nutrient concentration, rainfall, and root colonization (Osman, 2013).…”
Section: Discussionsupporting
confidence: 76%
“…As published in our previous study (Khan et al, 2021), results indicated that concentrations of N, P, Mg, Mn, Na, Zn, S, Al, and Fe generally increased with the level of decay across all three forest types, except for K and B in PAPF. The highest concentrations of N, P, B, Mg, K, C, Zn, and Mn in coarse wood debris (CWD) were found in BPF, while the highest concentrations of Fe and S were observed in PAPF and TPF, respectively.…”
Section: Nutrient Concentration Across Different Decay Classes and Fo...supporting
confidence: 84%
See 1 more Smart Citation
“…C and N concentrations are important factors that influence the decay of deadwood. CWD is crucial for forest productivity, nutrient cycling, carbon decomposition and sequestration, and forms a significant carbon pool in the forest ecosystem [12]. Soil, mulch, and downed logs are significant carbon pools that should be considered in programs aimed at reducing carbon emissions in arid regions [13].…”
Section: Resultsmentioning
confidence: 99%
“…Dominant species like Korean pine and Manchurian ash are mostly retained considering their high economic value. After thinning, the chopped trees were left in the plot to imitate the process of self-thinning, during which the dead trees or fallen trees would stay in the forests, becoming coarse wood debris and providing habitats and protection for various organisms such as insects and fungi (Bunnell and Houde, 2010;Khan et al, 2021). The tree codes of fallen trees were recorded to calculate the actual thinning intensities, which are 0% (CK), 17.25% (LT), 34.73% (MT) and 51.87% (HT) (Table 1).…”
Section: Thinning Treatments and Plot Inventorymentioning
confidence: 99%